(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2021)
The health care systems in resource limited countries are facing major challenges in dealing with Coronavirus disease (COVID-19). In Bangladesh, a steady increase in the number of COVID-19 cases since its first report on March 8, 2020, has led to an increased demand for COVID-19 detection facilities throughout the country. The detection of severe acute respiratory syndrome (SARS-CoV-2), the causative organism of COVID-19 and a highly infectious group 3(three) organism, requires a high biocontainment laboratory with a certain standard prerequisite infrastructure. This study describes the necessary steps for establishing and running a COVID-19 laboratory under resource constraint settings. Our experience indicates that, with collaborative efforts, funding, and technical support from locally available expertise, it is feasible to set up an optimally functional biocontainment facility with an acceptable quality performance despite several short comings. BSMMU J 2021; 14 (COVID -19 Supplement): 45-50